WORK IN THE 21ST CENTURY: THE CHANGING ROLE OF HUMAN RESOURCE MANAGERS - okolie, ugo CHUKS; EHEBHAMHEN, Airrykah Ehi (Indonesian Journal of Strategic Management, 2024)
This study examines the changing role of human resource managers in the 21st Century and the future of human resource management. There are an incredible number of pressures in today's organizations. To name a few: environmental pressures such as increasing globalization, rapid technological change, and tougher competition; organizational changes such as new organizational alliances, new structures and hierarchies, new ways of assigning work, and a very high rate of change; changes in the workforce, including employees' priorities, capabilities, and demographic characteristics.  HR managers were given extra duties as a consequence of the COVID-19 pandemic, including ensuring that new regulations are followed, arranging for employees to work from home, redesigning the workspace to make it safer for both onsite staff and clients, and putting a greater emphasis on mental health issues among employees. The department of human resources has a vital role to play in assisting organizations in navigating through these transitions because of the pressures they face. But to fulfill this role, HR will need to add more perceived and actual value. This study concluded that the working environment may never be the same again as new situations arise and old ones are resolved, necessitating organizational-wide adjustments at the managerial and strategic levels. In order to guarantee that a proactive and effective approach is employed for present and future obstacles, HR department can successfully function as the link between staff members and higher management.